Aspectos conceituais do processo de descrição: uma abordagem sob a ótica da Bibliografia e da Catalogação a partir do livro impresso - Vinicius de Souza Tolentino (2021)
Organization of Information, identified as a set of processes – selection, representation, and ordination – about documents, in a bibliographic approach, comes from Bibliography studies, librarianship, and documentation. The description is a process of representing, materialized initially in catalogs and bibliographies, especially regarding pressed book aspects, objective to individualize the object, through their characteristics. The Bibliography and Librarianship were constituted, markedly, from practical answers realized about and from the object book, although will not be defined these areas by the object book. A general objective proposes to explore the process of description in Bibliography and Cataloging disciplines from the pressed book, aiming to evidence their conceptual aspects. Characterized as qualitative research, theoretical nature; the object is bibliographic, and procedures, configures as a documental observation. Observe that Bibliography discipline constitutes a broad terrain of approaches, of which two orientations stand out, from diverse denominations, between then: Enumerative Bibliography and Analytical Bibliography. The Analytical Bibliography contributes for the description in information systems, fore detailing specific aspects of copies given the edition they represent. Enumerative Bibliography approaches the representation of documents in information systems under the Cataloging bias, but Bibliography, both aspects, were consolidated in the perspective of methods aimed at the specific objectives of each bibliographic project. In Cataloging, the emphasis to normative level, encouraged by international standardization programs and actions, and due to the predominance of the American culture of cataloging in libraries, it conducted towards a construct of a universal model of description, which to adopt in a very similar way in different institutions. Based on the book, this model taken as a universal reference does not privilege the pragmatic aspects that allowed contemplate the specificities of the audiences. Despite this, it is in the context of the Cataloging discipline that theoretical principles for description developed, based on the notion of work, in particular, edition and item/copy. It concluded that representation, worked on in the disciplines Bibliography and Cataloging, points to modalities structured according to determined common objectives. The description is a linguistic process that aims to communicate something, and the arrangement adopted in this process is based on a known structure serving as a reference.